CORPORATE GOVERNANCE DAN FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA - Steven Thamlim; Frestin Chrisnanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to examine the factors on earning management. These factors include audit quality, board of directors, firm size, audit committee, leverage, corporate governance, audit industry specialization, and audit tenure using absolute discretionary accruals to non-financial companies in Indonesia. The objects in this study are all non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2019. This study uses a purposive sampling method and obtains 954 sample. This study uses multiple linear regression to test the hypothesis. The results of this study indicate that the variables of audit quality, firm size, leverage, corporate governance, and audit tenure have influence toward earnings management. Meanwhile, board of directors, audit committee, and industry specialization audit have no influence on earnings management. The company's internal factors give more influence to the practice of earnings management, compared to factors originating from outside the company.